2012
DOI: 10.1002/app.38700
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of mechanical performance of compatibilized polypropylene/poly(ethylene terephthalate) blends via selective dispersion of halloysite nanotubes in the blend

Abstract: Many recycled plastics are the polypropylene (PP)/poly(ethylene terephthalate) (PET) blends with PET as the minor component. The modification of such kinds of PP/PET blends for higher performance is essential as PP and PET are not thermodynamically compatible. In this study, the elastomer, SEBS-g-MAH, and the inorganics, halloysite nanotubes (HNTs) are chosen as the modifiers for the modification of a model PP/PET blend (90/10). The mechanical performance of such blend is optimized by the selective dispersion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…HNTs modified with N ‐( β ‐aminoethyl)‐ γ ‐aminopropyltrimethoxysilane were used to compatibilize a polyoxymethylene/polypropylene (PP) blend and a syndiotactic PS/liquid crystalline polymer blend . HNTs were also used with maleated styrene–ethylene/butylene–styrene to improve the performances of a PP/poly(ethylene terephthalate) blend . However, there are no reports about the use of inner‐surface‐functionalized halloysite in immiscible polymer blends.…”
Section: Introductionmentioning
confidence: 99%
“…HNTs modified with N ‐( β ‐aminoethyl)‐ γ ‐aminopropyltrimethoxysilane were used to compatibilize a polyoxymethylene/polypropylene (PP) blend and a syndiotactic PS/liquid crystalline polymer blend . HNTs were also used with maleated styrene–ethylene/butylene–styrene to improve the performances of a PP/poly(ethylene terephthalate) blend . However, there are no reports about the use of inner‐surface‐functionalized halloysite in immiscible polymer blends.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Lin [69] confirmed that the addition of unmodified HNTs and compatibilizer (SEBS-g-MAmaleic anhydride grafted styrene -ethylene -butylene -styrene block copolymer) is an effective way to improve interfacial adhesion in PP/PET blends. However, HNTs were well dispersed only in the blend prepared as a two-step process, i.e.…”
Section: Other Methods Of Homogeneity Improvement In Polyolefin/hnt Nmentioning
confidence: 99%
“…Moreover, beside single polyolefin systems, HNTs are also used in blends of polyolefins with other polymers. Lin [69] stated that the formation of an unique morphology with encapsulation structure (Fig. 10) during two-step processing of PP/PET/SEBS-g-MAH/HNTs blend was crucial for substantial improvement of the mechanical performance of PP/PET blends.…”
Section: Mechanical Properties Of Polyolefin/hnt Nanocompositesmentioning
confidence: 99%
“…1,2 In polymerblend systems, poor color stability could be caused by phase separation. A possible solution to this problem is the addition of nanometric particles which includes carbon nanotubes, 3 silica beads, 4,5 halloysite nanotubes 6 and organoclays. [7][8][9] The use of nanoparticles is a viable route for manipulating both the interfacial tension and the viscosity ratio of multiphase non-conjugated polymeric materials.…”
Section: Introductionmentioning
confidence: 99%